Diagnostic Accuracy of Stress Myocardial Perfusion Imaging Compared to Invasive Coronary Angiography With Fractional Flow Reserve Meta-Analysis. (January 2015) - Takx, Richard A.P.; Blomberg, Björn A.; El Aidi, Hamza; Habets, Jesse; de Jong, Pim A.; Nagel, Eike; Hoffmann, Udo; Leiner, Tim
<x xml:space="preserve">Abstract</x> Background— Hemodynamically significant coronary artery disease is an important indication for revascularization. Stress myocardial perfusion imaging is a noninvasive alternative to invasive fractional flow reserve for evaluating hemodynamically significant coronary artery disease. The aim was to determine the diagnostic accuracy of myocardial perfusion imaging by single-photon emission computed tomography, echocardiography, MRI, positron emission tomography, and computed tomography compared with invasive coronary angiography with fractional flow reserve for the diagnosis of hemodynamically significant coronary artery disease. Methods and Results— The meta-analysis adhered to the Preferred Reporting Items for Systematic Reviews and Meta-analyses statement. PubMed, EMBASE, and Web of Science were searched until May 2014. Thirty-seven studies, reporting on 4721 vessels and 2048 patients, were included. Meta-analysis yielded pooled sensitivity, pooled specificity, pooled likelihood ratios (LR), pooled diagnostic odds ratio, and summary area under the receiver operating characteristic curve. The negative LR (NLR) was chosen as the primary outcome. At the vessel level, MRI (pooled NLR, 0.16; 95% confidence interval [CI], 0.13–0.21) was performed similar to computed tomography (pooled NLR, 0.22; 95% CI, 0.12–0.39) and positron emission tomography (pooled NLR, 0.15; 95% CI, 0.05–0.44), and better than single-photon emission computed tomography (pooled NLR, 0.47; 95% CI, 0.37–0.59). At the patient level, MRI (pooled NLR, 0.14; 95% CI, 0.10–0.18) performed similar to computed tomography (pooled NLR, 0.12; 95% CI, 0.04–0.33) and positron emission tomography (pooled NLR, 0.14; 95% CI, 0.02–0.87), and better than single-photon emission computed tomography (pooled NLR, 0.39; 95% CI, 0.27–0.55) and echocardiography (pooled NLR, 0.42; 95% CI, 0.30–0.59). Conclusions— Stress myocardial perfusion imaging with MRI, computed tomography, or positron emission tomography can accurately rule out hemodynamically significant coronary artery disease and can act as a gatekeeper for invasive revascularization. Single-photon emission computed tomography and echocardiography are less suited for this purpose.